1994
DOI: 10.1039/p29940001545
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of triethylamine–acid chloride charge-transfer complexes

Abstract: 695 01 9, India Charge-transfer (CT) complexes formed between various para-substituted benzoyl chlorides and triethylamine in acetonitrile have been studied spectrophotometrically. Photoactivation of these CT complexes lead to products arising from the reactions of acyl and aminoalkyl radicals. These photochemical processes have been utilized to generate acyl radicals from 0-allylsalicylyl chloride which undergoes intramolecular cyclization to form 3-methylchroman-4-one 20 in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Triethylamine (TEA), as an electron donor (D), can form n-p type complexes with electron acceptors (A), such as anhydride, acyl chlorides, and sulfonyl chlorides, involving a chargetransfer process. [14][15][16][17][18] In 1973, Mayahi and Elberman first reported the formation of charge-transfer complexes (CTCs) between maleic anhydride (MA) and TEA, and subsequently formed a zwitterionic product. 17 Such a reaction between anhydrides (ITA and MA) and TEA was further reported in 2010 by Wang et al, who suggested that both conjugation and a large difference in pKa value between the A and D were necessary for generating coloured complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Triethylamine (TEA), as an electron donor (D), can form n-p type complexes with electron acceptors (A), such as anhydride, acyl chlorides, and sulfonyl chlorides, involving a chargetransfer process. [14][15][16][17][18] In 1973, Mayahi and Elberman first reported the formation of charge-transfer complexes (CTCs) between maleic anhydride (MA) and TEA, and subsequently formed a zwitterionic product. 17 Such a reaction between anhydrides (ITA and MA) and TEA was further reported in 2010 by Wang et al, who suggested that both conjugation and a large difference in pKa value between the A and D were necessary for generating coloured complexes.…”
Section: Introductionmentioning
confidence: 99%
“…As an electron donor, TEA or pyridine forms n −π type complexes with electron acceptors such as alkyl halides, sulfonyl chlorides, and acyl chlorides, involving proton/charge transfer. Under photoirradiation, TEA can also react with methylene chloride and C 60 . , Known as the Einhorn reaction, much attention was paid in the past to the formation of intermediate ketenes and the double bond shift from the α,β- to the β,γ-position in the alcoholysis of α,β-unsaturated acyl chlorides such as crotonoyl chloride with tertiary amines, such as TEA and pyridine. The reaction of TEA with maleic anhydride (MA) was first reported by Mayahi and El-Bermani to yield a yellow solution first and then a dark brown solid in a few minutes . Such reaction between tertiary and primary amines with cyclic anhydrides was further investigated in terms of kinetics. , Though extensive, the above studies were not performed on the esterification of hydroxyl-containing polymers, and therefore, little attention was paid to how such complexation would affect the properties and biological performance of the polymers resulted.…”
Section: Introductionmentioning
confidence: 99%
“…As an electron donor, TEA or pyridine forms n-π type complexes with electron acceptors such as alkyl halides, sulfonyl chlorides, and acyl chlorides, involving proton/charge transfer. [9][10][11][12][13] Under photoirradiation, TEA can also react with methylene chloride and C 60 . 14,15 Known as the Einhorn reaction, 16 much attention was paid in the past to the formation of intermediate ketenes and the double bond shift from the R,βto the β,γ-position in the alcoholysis of R,β-unsaturated acyl chlorides such as crotonoyl chloride with tertiary amines, such as TEA and pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of UV light limited its further applications with only one type of intramolecular cyclization of o -allylsalicylyl chloride being achieved. Furthermore, the corresponding mechanism remains unclear . Herein, we report new examples of CTC-enabled SET from LB to acyl chlorides under blue light irradiation for the synthesis of various acylated heterocycles.…”
mentioning
confidence: 96%